Misspecification tests in econometrics : the Lagrange multiplier principle and other approaches - Godfrey, L. G. (Cambridge, Cambridgeshire ; New York : Cambridge University Press, 1988)
Misspecification tests play an important role in detecting unreliable and inadequate economic models. This book brings together many results from the growing literature in econometrics on misspecification testing. It provides theoretical analyses and convenient methods for application. The main emphasis is on the Lagrange multiplier principle, which provides considerable unification, although several other approaches are also considered. The author also examines general checks for model adequacy that do not involve formulation of an alternative hypothesis. General and specific tests are discussed in the context of multiple regression models, systems of simultaneous equations, and models with qualitative or limited dependent variables.
Includes index.
Includes bibliographical references: p. 232-245.
rpm 25/09/2017
Loans
Keywords: Econometrics; Econometric models; Multiplier (Economics)